A randomized trial comparing the efficacy of cognitive–behavioral therapy for bulimia nervosa delivered via telemedicine versus face-to-face - Mitchell, James E. (2008)
OBJECTIVE: A major problem in the delivery of mental health services is the lack of availability of empirically supported treatment, particularly in rural areas. To date no studies have evaluated the administration of an empirically supported manual-based psychotherapy for a psychiatric condition via telemedicine. The aim of this study was to compare the relative efficacy and acceptability of a manual-based cognitive–behavioral therapy (CBT) for bulimia nervosa (BN) delivered in person to a comparable therapy delivered via telemedicine. METHOD: One hundred twenty-eight adults meeting DSM-IV criteria for BN or eating disorder—not otherwise specified with binge eating or purging at least once per week were recruited through referrals from clinicians and media advertisements in the targeted geographical areas. Participants were randomly assigned to receive 20 sessions of manual-based, CBT for BN over 16 weeks delivered either face-to-face (FTF-CBT) or via telemedicine (TV-CBT) by trained therapists. The primary outcome measures were binge eating and purging frequency as assessed by interview at the end of treatment, and again at 3- and 12-month follow-ups. Secondary outcome measures included other bulimic symptoms and changes in mood. RESULTS: Retention in treatment was comparable for TV-CBT and FTF-CBT. Abstinence rates at end-of-treatment were generally slightly higher for FTF-CBT compared with TV-CBT, but differences were not statistically significant. FTF-CBT patients also experienced significantly greater reductions in eating disordered cognitions and interview-assessed depression. However, the differences overall were few in number and of marginal clinical significance. CONCLUSIONS: CBT for BN delivered via telemedicine was both acceptable to participants and roughly equivalent in outcome to therapy delivered in person.